The overlook: a novel (Harry Bosch mysteries, 13, 1, 2008)
From bestselling author Connelly comes this electrifying new Harry Bosch novel. In his first case since he left the LAPDs Open Unsolved Unit for the Homicide Special squad, Bosch is called out to investigate a murder that may have chilling consequences for national security.

The narrows: a novel (Harry Bosch mysteries, 10, 1, 2005)
Former LAPD Detective Harry Bosch investigates the death of an old friend who had ties to the hunt for the infamous serial killer, The Poet. What Harry finds leads him into the most terrifying situation he has ever encountered.

The Drop (Harry Bosch mysteries, 15, 1, 2011)
Detective Harry Bosch investigates a cold case and the murder of a city councilman's son. The cases are unrelated but they twist around each other like the double helix of a DNA strand. One leads to the discovery of a killer operating in the city for as many as three decades; the other to a deep political conspiracy that reached back into the dark history of the police department.

The Harry Bosch novels (Harry Bosch mysteries, 2, 1, 2001)
Description Not Provided